Pemanfaatan Limbah Rumah Tangga Sebagai Pupuk Organik Cair (Poc) Untuk Budidaya Tanaman Tomat - Muhidin Muhidin; Gusti R. Sadimantara; Nini Mila Rahni; Dewi Nurhayati Yusuf; Dedi Erawan; Sitti Leomo; Gusti Ayu Kade Sutariati; Tresjia Corina Rakian; Waode Nuraida (Jurnal Pengabdian Masyarakat Ilmu Terapan, 2023)
This PKMI activity will apply environmentally friendly POC (liquid organic fertilizer) technology to the people who live in Wakadia Village, Muna Regency. Wakadia village is an agricultural area with land conditions that grow vegetables yearly using chemical fertilizers. The chemical fertilizer will have an impact on decreasing the condition of soil nutrients and have an impact on the health of the people of Wakadia village. In this New Normal era, healthy and nutritious nutrition is urgently needed to increase the resistance or immunity of the local community, so to fulfill this nutrition, organic vegetables that are free of chemicals are needed. Therefore, POP technology is needed to improve the quality of soil nutrients, increase production and obtain organic vegetable crops. In the village of Wakadia there are also many agricultural wastes and household wastes that are abundant but have not been optimally processed so they do not provide added value to the village community, so this PKM activity must be carried out to improve environmental conditions that have been polluted due to the use of chemical fertilizers. , and can also increase the local community's income by utilizing existing waste as organic fertilizer, where organic fertilizer has a higher price than unprocessed livestock manure. Thus, the solution offered in this PKMI activity is the application of technology in changing the use of chemical fertilizers with POC technology so that farming land is even more productive. The forms of technology applied to the community in this service are (1) technology for making liquid organic fertilizer, (2) technology for packaging liquid organic fertilizer (3) technology for marketing tomato plants through online media (Facebook and WhatsApp).